Biopolymers and Biomaterials - Padinjakkara, Aneesa; Thankappan, Aparna; Souza, Jr., Fernando Gomes; Thomas, Sabu (Apple Academic Press, 2018)
Biopolymers are attracting immense attention of late because of their diverse applications that can address growing environmental concerns and energy demands. The development of various biomaterials creates significant advancements in the medical field as well, and many biopolymers are used for the fabrication of biomaterials. Together, biopolymers and biomaterials create great potential for new materials, applications, and uses. This new volume, Biopolymers and Biomaterials, covers the science and application of biopolymers and biomaterials. It presents an array of different studies on biopolymers and biomaterials, along with their results, interpretation, and the conclusions arrived at through investigations. It includes biopolymer synthesis, their characterizations, and their potential applications. The book begins with an explanation of the different biopolymers used in the textile industry, their advantages and disadvantages, and their applications